The effect of plant density on the growth and seed yield of fenugreek (Trigonella foenum graecum L.) - Ahmad, Mahmod K.; Abdulla, Anwar R. (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study was conducted to determine the effects of different plant and row spacing (20*20 as T1, 30*30 as T2 and 40*40 as T3 cm) on the growth and yield of fenugreek (Trigonella foenum graecum L.) in Bakrajo – Sulaimani in the autumn season of (2013-2014).This simple field experiment was arranged in RCBD within three replication at the experimental fields of Bakrajo Technical Agricultural Institute–Sulaimani Polytechnic University. As a result of the research, while all the growth and yield parameters except dry root weight were significantly affected by plant and row spacing applications, significant increased in plant height (68.067) cm seed yield (1407.267) kg/ha was resulted from (20) cm plant and row spacing. While number of branches per plant (13.233), the dry weight of vegetative (57.867) gm, number of pod per plant (70.133), number of seeds per pod (17.13) and thousand-seed weight (14.6) gm, was resulted from (40) cm plant and row spacing.
Keywords: Density; Yield Fenugreek